Baicalein inhibits PRRSV through direct binding, targeting EGFR, and enhancing immune response - Jing Wu; Qi Lu; Jing Hou; Yueqin Qiu; Min Tian; Li Wang; Kaiguo Gao; Xuefen Yang; Zongyong Jiang (Veterinary Research)
Abstract Porcine reproductive and respiratory syndrome virus (PRRSV) presents significant economic challenges to the global pork industry due to its ability to mutate rapidly. The current commercial vaccines have limited effectiveness, and there are strict restrictions on the use of antiviral chemical drugs. Therefore, it is urgent to identify new strategies for preventing and controlling PRRSV infections. Baicalein, a flavonoid derived from Scutellaria baicalensis, has gained attention for its potential antiviral properties. However, there is little information about the effects and mechanisms of baicalein in relation to PRRSV. In this study, a network pharmacology analysis identified seven potential targets of baicalein against PRRSV, with the epidermal growth factor receptor (EGFR) emerging as the core target. The results of molecular docking and dynamics (MD) simulations confirmed that baicalein has a high binding affinity for EGFR, with a measured value of − 7.935 kcal/mol. Additionally, both in vitro (EC50 = 10.20 μg/mL) and in vivo (2.41 mg/kg) experiments were conducted to assess the effectiveness of baicalein against PRRSV. Notably, baicalein was found to inhibit various stages of the PRRSV replication cycle and could directly bind to PRRSV in vitro. Baicalein inhibited the entry of PRRSV by blocking EGFR phosphorylation and the downstream PI3K-AKT signaling pathway. This was confirmed by a decrease in the expression of p-EGFR/EGFR, p-AKT/AKT, PI3K, and SRC following treatment with baicalein. Additionally, baicalein significantly enhanced the immune response in piglets infected with PRRSV. In conclusion, this study suggests that baicalein may be a promising pharmaceutical candidate for preventing and controlling PRRS, offering new insights into the antiviral potential of Chinese herbal medicine.